The role of plasticity in combined torsion and bending of elastic–plastic guidewires. (June 2021) - Shirazi, Reyhaneh N.; McGrath, Donnacha J.; Clancy, Marie; Higgins, Caroline; Mooney, Ivan; Dickenson, Roger C.; McHugh, Peter E.; Ronan, William
Abstract: Medical guidewires are typically subjected to combined bending and torsion and undergo large deformations past the point of initial yielding. Experimental and clinical use of guidewires report two undesirable phenomena: lag, where output rotation of the wire is less than the input rotation; and whip, where the output rotation rate suddenly increases. In the current study, we present a finite element model of a guidewire in an idealised tortuous path. This model is used to elucidate the relationship between material properties, in particular, the onset of yield and hardening behaviour, and these phenomena. Combined bending and torsion lead to cyclic strains locally in the wire. For yielding materials, plastic dissipation during cyclic loading means external work is necessary and a reaction moment develops. This moment resists rotation leading to the lag phenomenon. Subsequent strain hardening leads to whip, which increases with tangent modulus. Straight sections of wire ahead of the curved region are shown to increase the amount of whip observed. A simplified theoretical treatment explains the key trends and provides strategies to reduce the unwanted phenomena.